Rescue version of a carotid micro-endarterectomy: an ACE-ICA anastomosis with proximal Ica and distal ACE hemoclip obliteration. (3rd April 2023) - Bartoš, Robert; Hejčl, Aleš; Lodin, Jan; Sameš, Martin; Marek, Tomas
Abstract: Aim of the study : To present our rescue approach of carotid artery occlusion as well as to discuss other possible techniques that can be applied in similar situations.Materials and methods: Two cases from our institution with acute complications during carotid micro-endarterectomy (CEA).Results : Two cases from our institution with acute postoperative complications during CEA that were successfully addressed are presented with imaging and detailed description of the surgical techniques used.Conclusion : CEA are common surgical procedures pursued to achieve revascularization of carotid arteries when occluded partially or fully by an atherosclerotic plaque. As with any surgical procedure, associated complications exist in small percentage of the cases. These can include blood flow limitation due to an insufficient artery wall after atherosclerotic plaque extraction as well as distal kinking of the internal carotid artery. A direct end-to-end ACE-ACI bypass with occlusion of the proximal ACI and distal ACE stump preserves distal flow to the ACI, however the original arteriotomy of ACC must be completely sutured up to the arterial stumps.